Prevalence of Headache in Patients With Coronavirus Disease 2019 (COVID-19): A Systematic Review and Meta-Analysis of 14,275 Patients - Islam, Md Asiful; Alam, Sayeda Sadia; Kundu, Shoumik; Hossan, Tareq; Kamal, Mohammad Amjad; Cavestro, Cinzia (Frontiers in Neurology, 2020)
Background: Coronavirus disease 2019 (COVID-19) started to spread globally since December 2019 from Wuhan, China. Headache has been observed as one of the clinical manifestations in COVID-19 patients. We aimed to conduct a comprehensive systematic review and meta-analysis to estimate the overall pooled prevalence of headache in COVID-19 patients. Methods: PubMed, Scopus, ScienceDirect, and Google Scholar databases were searched to identify studies published between December 2019 and March 2020. Adult (≥18 years) COVID-19 patients were considered eligible. We used random-effects model to estimate the pooled prevalence with 95% confidence intervals (CIs). Quality assessment was done using the Joanna Briggs Institute (JBI) critical appraisal tools. This study is registered with PROSPERO (CRD42020182529). Results: We identified 2055 studies, of which 86 studies (n=14275, 49.4% female) were included in the meta-analysis. Overall, the pooled prevalence of headache in COVID-19 patients was 10.1% [95% CI: 8.76-11.49]. There was no significant difference of headache prevalence in severe or critical vs non-severe (RR: 1.05, p=0.78), survived (recovered or discharged) vs non-survived (RR: 1.36, p=0.23) and ICU vs non-ICU (RR: 1.06, p=0.87) COVID-19 patients. We detected 95.4% of the included studies as high-quality. Conclusions: From the first four-month data of the outbreak, headache was detected in 10.1% of the adult COVID-19 patients.